2021
DOI: 10.1101/2021.11.17.21266404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Care Models for Long COVID : A Rapid Systematic Review

Abstract: ContextMore than 18M people worldwide (150K Canadians) are living with Long COVID resulting in debilitating sequalae and disabilities that impact their quality of life and capacity to return to work. A new care model is needed for persons living with this complex and multi-systemic disease.ObjectivesWhat is the best-available evidence about care models for persons living with Long COVID?DesignRapid Living Systematic Review.MethodWe systematically searched seven electronic databases (MEDLINE, Embase, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
0
20
1
1
Order By: Relevance
“…22 This strategy is highly problematic for COVID-19, because many infected people will die of the disease, and many who survive have what is known as long COVID. 23 Second is the limited control case in which R is reduced to less than R 0 =2•4 but remains greater than 1. In this case, the epidemic still grows exponentially, but less rapidly than with no control measures.…”
Section: Four Covid-19 Control Regimesmentioning
confidence: 99%
“…22 This strategy is highly problematic for COVID-19, because many infected people will die of the disease, and many who survive have what is known as long COVID. 23 Second is the limited control case in which R is reduced to less than R 0 =2•4 but remains greater than 1. In this case, the epidemic still grows exponentially, but less rapidly than with no control measures.…”
Section: Four Covid-19 Control Regimesmentioning
confidence: 99%
“…The PCS has led healthcare organizations to develop new care units with multidisciplinary teams, in which rehabilitation services play a key role 11 , 12 . A systematic review analysing 12 international models of PCS care has shown that most of them include primary care and/or specialized clinics, and they all include rehabilitation services tailored to the patient’s needs 13 . With regard to assessment, the COVID-19 Yorkshire Rehabilitation Scale (C19-YRS), the Newcastle post-COVID screening tool and the Post-COVID-19 Functional Status scale (PCFS), have been proposed to track functional outcomes in patients affected by this complex multi-organ disorder 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…Posters, advertisements, and snowball sampling will target those who lack resources or technology to be recruited via online messages; they can contact us by telephone or email. Collaborators will provide recruitment and data collection support through organizations such as Born in Bradford (BiB) in Yorkshire, a long COVID center [ 85 ] in Gateshead, the Bromley-by-Bow community center in East London, and migrant charities in London and Canterbury.…”
Section: Methodsmentioning
confidence: 99%